2006
DOI: 10.1063/1.2387978
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of near-interface traps in Al2O3∕4H-SiC and Al2O3∕SiO2∕4H-SiC structures

Abstract: Aluminum oxide (Al2O3) has been grown by atomic layer deposition on n-type 4H-SiC with and without a thin silicon dioxide (SiO2) intermediate layer. By means of Capacitance Voltage and Thermal Dielectric Relaxation Current measurements, the interface properties have been investigated. Whereas for the samples with an interfacial SiO2 layer the highest near-interface trap density is found at 0.3 eV below the conduction band edge, Ec, the samples with only the Al2O3 dielectric exhibit a nearly trap free region cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The most widely used passivation for 4H-SiC devices is thermally grown oxide SiO 2 . Nevertheless, with higher dielectric constant and better thermal stability, Al 2 O 3 draws more and more attention as passivation and gate dielectric material on 4H-SiC devices in recent years [1][2][3]. In another respect, SiO 2 and Al 2 O 3 are the most important oxide film materials for optical coatings in the DUV spectral region [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used passivation for 4H-SiC devices is thermally grown oxide SiO 2 . Nevertheless, with higher dielectric constant and better thermal stability, Al 2 O 3 draws more and more attention as passivation and gate dielectric material on 4H-SiC devices in recent years [1][2][3]. In another respect, SiO 2 and Al 2 O 3 are the most important oxide film materials for optical coatings in the DUV spectral region [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The latter was shown by TDRC measurements of 1273 K (Ar) annealed (∼100 nm) Al 2 O 3 /4H-SiC capacitors. [20] www.interscience.wiley.com/journal/sia …”
Section: Methodsmentioning
confidence: 99%
“…In fact, annealing in Ar above the crystallization temperature ͑ϳ900°C͒ was found to significantly enhance the electrical properties of the Al 2 O 3 / SiC interface and promote formation of the ␥ phase of Al 2 O 3 . Furthermore, it has been revealed that the interface properties of those annealed structures are superior to the ones of SiO 2 /4H-SiC interfaces, since the density of electron traps close to the conduction band minimum is reduced, 4 as required for improved channel mobility in a metal-oxide-SiC field effect transistors. In this study, the Al 2 O 3 /4H-SiC interface was investigated on as-grown and annealed samples using angle resolved x-ray photoelectron spectroscopy ͑AR-XPS͒, transmission electron microscopy ͑TEM͒, and secondary ion mass spectrometry ͑SIMS͒.…”
mentioning
confidence: 99%
“…1,2 It has been shown that high quality Al 2 O 3 films can be grown on SiC by atomic layer chemical vapor deposition ͑ALCVD͒. 3 In previous studies, [4][5][6] electrical characterization such as capacitancevoltage ͑CV͒ and thermal dielectric relaxation current measurements of Al 2 O 3 /4H-SiC capacitors were reported. In fact, annealing in Ar above the crystallization temperature ͑ϳ900°C͒ was found to significantly enhance the electrical properties of the Al 2 O 3 / SiC interface and promote formation of the ␥ phase of Al 2 O 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation